Cerebral Venous Infarction: A Potentially Avoidable Complication of Deep Brain Stimulation Surgery - Morishita, Takashi (2013)
OBJECT: Despite numerous reports on the morbidity and mortality of deep brain stimulation (DBS), cerebral venous infarction has rarely been reported. We present four cases of venous infarct secondary to DBS surgery. METHODS: The diagnosis of venous infarction was based on: 1) delayed onset of new neurologic deficits on post-operative day 1 or 2, and 2) significant edema surrounding the superficial aspect of the implanted lead, with or without subcortical hemorrhage on CT scan. RESULTS: Four cases (0.8%/lead, 1.3%/patient) of symptomatic cerebral venous infarction were identified out of 500 DBS lead implantation procedures between July 2002 and August 2009. All four patients had Parkinson’s disease (PD). Their DBS leads were implanted in the subthalamic nucleus (STN) (n=2), and the internal globus pallidus (GPi) (n=2). Retrospective review of the targeting confirmed that the planned trajectory passed within 3mm of a cortical vein in two cases for which contrast-enhanced pre-operative MRI was available. In the other two cases, contrasted targeting images were not obtained preoperatively. CONCLUSION: Cerebral venous infarction is a potentially avoidable, but serious complication. To minimize its incidence, we propose the use of high resolution, contrast-enhanced, T1 weighted MR images to delineate cerebral venous anatomy, along with careful stereotactic planning of the lead trajectory to avoid injury to venous structures.